A Clinical and Radiographic Evaluation of Zirconia Dental Implants: 10-Year Follow-Up - Andrea Enrico Borgonovo; Susanna Ferrario; Carlo Maiorana; Virna Vavassori; Rachele Censi; Dino Re (International Journal of Dentistry)
Purpose. The aim is to evaluate the survival and success rates, as well as the marginal bone loss (MBL) and periodontal indexes, of zirconia implants with 10-year follow-up. Materials and Methods. 10 patients were selected and 26 one-piece zirconia implants were used for the rehabilitation of single tooth or partially edentulous ridge. After 10 years, a clinical-radiographic evaluation was performed in order to estimate peri-implant tissue health and marginal bone loss. Results. The survival and success rates were 100%. The average marginal bone loss from baseline to 120 months after surgery was 0.92 ± 0.97 mm. Conclusion. One-piece zirconia dental implants are characterised by high biocompatibility, low plaque adhesion, and absence of microgap that can be related to the clinical success of these implants.